Analysis of the Effect of Profitability, Solvency, and Activity Ratios on Firm Value in Conventional Banks in Indonesia During the 2021–2024 Period - Araujo, Delia Iria Magno de; Pandin, Maria Yovia R; Kusmaningtyas, Amiartuti (Sean Institute, 2025)
This study aims to analyze the effect of profitability, solvency, and activity ratios on firm value in conventional banks listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The financial ratios examined include Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER), while firm value is measured using stock prices. The research employs a quantitative approach with multiple linear regression analysis, supported by SPSS version 27. Data were collected from audited annual reports of 15 conventional banks selected through purposive sampling. The results indicate that ROA, ROE, and DER have a significant simultaneous and partial influence on stock prices. The regression model passes all classical assumption tests and demonstrates an R² value of 0.68, meaning 68% of the variation in stock prices can be explained by the three financial ratios. These findings highlight the importance of financial performance as a determinant of firm value in the banking sector.